Self-regulation and performance among elite youth soccer players: the role of approach-avoidance motivation - Hamoud, M.; Sæther, S. A.; Bjørnebekk, G. (Frontiers in Psychology, 2024)
Introduction and methods: This study aimed to investigate the motivational processes behind self-regulated learning and performance among 192 soccer players (82 girls) for three age groups (14-16 years old) eligible for the Norwegian national football team. A conditional process model was proposed and tested with achievement goals as mediators between achievement motives on the one hand and coach-reported performance and self-regulated learning on the other hand. The probability of success was examined as a potential moderator in the motivational process.